Typologia reżimu odpływu rzek w Polsce w podejściu nadzorowanym i nienadzorowanym - Wrzesiński, Dariusz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2017)
The paper presents a typology of the river regime in Poland obtained with the application of a supervised approach, i.e. a classic typology according to the assumptions of Dynowska with a regime typology obtained in an unsupervised approach by means of hierarchical grouping. In both cases, the explanatory variables were monthly flow coefficients – respectively: only from spring and summer months, with predefined threshold values, or 12-month flow coefficients. The paper applied daily flow values from the period 1971-2010 for 516 gauges located on 280 Polish rivers. In both approaches, five types of regime were designated, including rivers characterised by a similar distribution and range of monthly runoff values in an average annual cycle. The designated groups, however, differ in abundance, which affects the image of spatial distribution of rivers representing the types of regime identified. The analysis shows that irrespective of the adopted method of designation, two types of regime, namely nival poorly developed and pluvio-nival are evidently characterised by different patterns of flow variability in an average annual cycle, and concern similar groups of rivers.
Keywords: river runoff; hydrological regime; hierarchical clustering; flow coefficient (Pardé)